Raman Spectroscopy in Group IV Nanowires and Nanowire Axial Heterostructures. Issue 1659 (2014) - Anaya, J.; Torres, A.; Jiménez, J.; Rodríguez, A.; Rodríguez, T.; Ballesteros, C.
ABSTRACT: The control of the SiGe NW composition is fundamental for the fabrication of high quality heterostructures. Raman spectroscopy has been used to analyse the composition of SiGe alloys. We present a study of the Raman spectrum of SiGe nanowires and SiGe/Si heterostructures. The inhomogeneity of the Ge composition deduced from the Raman spectrum is explained by the existence of a Ge-rich outer shell and by the interaction of the NW with the electromagnetic field associated with the laser beam.